2022
DOI: 10.5498/wjp.v12.i2.264
|View full text |Cite
|
Sign up to set email alerts
|

Insights into myelin dysfunction in schizophrenia and bipolar disorder

Abstract: Schizophrenia and bipolar disorder are disabling psychiatric disorders with a worldwide prevalence of approximately 1%. Both disorders present chronic and deteriorating prognoses that impose a large burden, not only on patients but also on society and health systems. These mental illnesses share several clinical and neurobiological traits; of these traits, oligodendroglial dysfunction and alterations to white matter (WM) tracts could underlie the disconnection between brain regions related to their symptomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 192 publications
(295 reference statements)
1
26
0
Order By: Relevance
“…Previous studies have shown that OLs and their precursors are vulnerable to inflammation, oxidative stress and elevated glutamate levels [69], which explains why these cells are affected in multiple neuropathological entities, including Alzheimer's disease, spinal cord injury, Parkinson's disease, and ischemia, as well as during hypoxia [70,71]. OL deficits have also been previously reported in schizophrenia and bipolar disorder [72,73] and direct evidence of altered oxidative stress markers has been detected in OLs from MDD suicide postmortem brain tissues [74]. The coincidence of gene expression patterns between upregulation of immune response and down regulation of maturation of OLs in suicide decedents in our study might suggest a causal relationship between the two.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have shown that OLs and their precursors are vulnerable to inflammation, oxidative stress and elevated glutamate levels [69], which explains why these cells are affected in multiple neuropathological entities, including Alzheimer's disease, spinal cord injury, Parkinson's disease, and ischemia, as well as during hypoxia [70,71]. OL deficits have also been previously reported in schizophrenia and bipolar disorder [72,73] and direct evidence of altered oxidative stress markers has been detected in OLs from MDD suicide postmortem brain tissues [74]. The coincidence of gene expression patterns between upregulation of immune response and down regulation of maturation of OLs in suicide decedents in our study might suggest a causal relationship between the two.…”
Section: Discussionmentioning
confidence: 88%
“…Ultimately, dysregulation of energy metabolism and lipids metabolism entails to overproduction of reactive oxygen species and immune response. Dysregulation of redox-responsible proteins, including PRDX6, GFAP, MDH and ATPase subunits, have been repeatedly identified in plasma and prefrontal cortex of patients with schizophrenia [41][42][43] . Unfortunately, researchers pay little attention to mechanisms instructing the pathogenesis of schizophrenia.…”
Section: Governors Of Oxidative Stress and Immunoreactivitymentioning
confidence: 99%
“…Despite the role elicited by Olig2 in the adult cerebral cortex under pathological conditions is not yet known, its reduced expression seems to switch cell fate from differentiation to death, contributing to the development of psychiatric disorders and acute/chronic neurodegenerative diseases, including Alzheimer’s disease and Amyotrophic Lateral Sclerosis, while its increased expression has been associated with different brain tumors, supporting its potential utility as therapeutic target for the treatment of both cancer and neurodegeneration [ 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 ]. Of note, several evidence showed that Olig2 deficiency as well as the presence of rare genetic polymorphisms in this gene (i.e., rs1059004) may represent risk factors for cognitive disorders and schizophrenia, through an effect on neuroanatomical connectivity ( Figure 2 ) [ 159 , 164 , 172 , 173 , 174 , 175 , 176 ].…”
Section: Cracking the Transcriptional Regulatory Programs Of Neuronal...mentioning
confidence: 99%